Multicultural Female Identity in Jean Kwok’s Novel Girl in Translation - Tsabita Tuffahati; Suardi, Suardi (ITScience (Information Technology and Science), 2025)
The study explores the power relations embedded within the construction of female identity in Girl in Translation, a novel portraying the immigrant experience of Kimberly, a young Chinese girl who relocates to Brooklyn, New York. Confronted by cultural barries and socioeconomic hardship, Kimberly’s journey reveals tensions surrounding gender and societal expectations. Employing a qualitative approach under a constructivist paradigm, this reasearch applies Michel Foucault’s theory of power to analyze the depiction of gender dynamics in the narrative. The findings indicate two distinct manifestation of power; epistemic power, shaped through discourse and informal knowledge, and corporeal power, exercised over the body. These forms of domination influence patterns of thought and behavior within male-female relationships, as illustrated through Kimberly’s personal and social interactions. Ultimately, the study highlights how the novel critiques normative structures and foregrounds the subtle mechanisms of control within everyday life.